DESAIN WEB-BASED SISTEM INFORMASI PENJUALAN MOBIL BEKAS - Pramitha Dwi Larasati; Ari Irawan; Afif Raihan Ismail; Fharadysia Nabila Abidin (Universitas Tridharma, 2021)
The considerable competition and the limited capacity of cars in the showroom have limited the number of cars that customers can see. Promotion systems that still use strategic locations and countable partners make promotions less effective. The emergence of COVID-19 which has become a epidemic in Indonesia and the coverage area which is still limited to certain locations is a hot topic of conversation in the community to use private cars. The purpose of this research is to create a web-based car sales system that can solve the problems at hand. The system design in this study uses the waterfall method. The waterfall method is a systematic traditional software development method. By using this method, research has been carried out, among others, System Planning, System Analysis up to the System Design stage. Web-based Car sales systems provide new opportunities, one of which is by accommodating a larger number of cars, digital transactions, and the convenience of people selling cars by posting photos and car specifications on the company's web-based sales page without having to show off the car in the showroom. Keywords—Waterfall Method, Car Sales System, Web-Based